2017
DOI: 10.3171/2016.9.spine15959
|View full text |Cite
|
Sign up to set email alerts
|

Post–spinal cord injury astrocyte-mediated functional recovery in rats after intraspinal injection of the recombinant adenoviral vectors Ad5-VEGF and Ad5-ANG

Abstract: OBJECTIVEThe most actively explored therapeutic strategy for overcoming spinal cord injury (SCI) is the delivery of genes encoding molecules that stimulate regeneration. In a mouse model of amyotrophic lateral sclerosis and in preliminary clinical trials in patients with amyotrophic lateral sclerosis, the combined administration of recombinant adenoviral vectors (Ad5-VEGF+Ad5-ANG) encoding the neurotrophic/angiogenic factors vascular endothelial growth factor ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 35 publications
1
7
0
1
Order By: Relevance
“…Similar to our study on mini pig, we found functional improvement in rats with SCI after intrathecal administration of adenoviral vectors or genetically engineered UCB-MCs with two combinations of therapeutic genes: (1) VEGF+GDNF+NCAM and (2) VEGF+ANG+NCAM that was demonstrated based on Basso-Beattie-Bresnahan (BBB) score. The pattern of motor recovery in gene-treated groups was consistent with our previous studies showing improvement after intraspinal injection of Ad5-VEGF+Ad5-ANG vectors on BBB score (Povysheva et al, 2017 ). Thus, intrathecal delivery of the therapeutic genes was found to be as effective as intraspinal approach of gene administration.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to our study on mini pig, we found functional improvement in rats with SCI after intrathecal administration of adenoviral vectors or genetically engineered UCB-MCs with two combinations of therapeutic genes: (1) VEGF+GDNF+NCAM and (2) VEGF+ANG+NCAM that was demonstrated based on Basso-Beattie-Bresnahan (BBB) score. The pattern of motor recovery in gene-treated groups was consistent with our previous studies showing improvement after intraspinal injection of Ad5-VEGF+Ad5-ANG vectors on BBB score (Povysheva et al, 2017 ). Thus, intrathecal delivery of the therapeutic genes was found to be as effective as intraspinal approach of gene administration.…”
Section: Discussionsupporting
confidence: 90%
“…Simultaneous delivery of various therapeutic genes into post-traumatic spinal cord may not only support the viability of affected injury cells and stimulate their regeneration, but also influence different mechanisms of the SCI including inflammation, demyelination, astrogliosis, and others (Lim et al, 2010 ; Walthers and Seidlits, 2015 ). Currently, several therapeutic genes are considered to be effective for single gene therapy, i.e., encoding neurotrophic BDNF (Nakajima et al, 2007 ), NGF (Romero et al, 2001 ), GDNF (Chou et al, 2014 ), growth VEGF, FGF (De Laporte et al, 2011 ), Angiogenin (Povysheva et al, 2017 ), anti-apoptotic BCL-2, BCL-XL (Yukawa et al, 2002 ), and anti-inflammatory IL-10, IL-1RA (Zhou et al, 2009 ) factors, and cell adhesion NCAM and L1 molecules (Chaudhry et al, 2006 ; Thuret et al, 2006 ; Walthers and Seidlits, 2015 ). The search for the best single candidate or the optimal combinations of several therapeutic genes is particularly important for translation of the gene therapy strategy to clinic.…”
Section: Introductionmentioning
confidence: 99%
“…In this relatively younger and wide spectrum of pre-middle age groups, anti-VEGF approaches have been proposed because the endogenous level of VEGF has not declined in the parenchyma adjacent to cerebral ventricles and in the cerebrospinal fluid (CSF). The neuroprotective effect of VEGF in cerebrovascular diseases is appreciated but the causal role of VEGF in the cerebral vasculature and ventricles has just begun to be revealed [ 8 , 12 , 16 , 18 , 19 , 20 , 22 , 24 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Vegf Signaling In Cerebrovascular Diseasesmentioning
confidence: 99%
“…However, such a clinical report alone displaying VEGF as a biomarker (total human sample size, 171) is not sufficient to determine an appropriate therapeutic approach of pro-VEGF or anti-VEGF drugs. As described in this section, for clinical decision making of pro-VEGF therapy, however, a methodological advancement of delivering VEGF [ 30 , 51 , 52 ] or inducing endogenous VEGF-like trophic factors [ 49 , 58 ] are expected to achieve a more effective modulatory outcome of neuroprotection in the cerebrovascular disease.…”
Section: Vegf Signaling In Cerebrovascular Diseasesmentioning
confidence: 99%
“…Н.Ф. Гамалеи (Москва) [5]. В настоящем исследовании были исполь-зованы Ad5, несущие репортёрный ген зелё-ного флюоресцирующего белка (Ad5-GFP).…”
Section: экспериментальная медицинаunclassified